2020
DOI: 10.5049/ebp.2020.18.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole-induced Severe Hyperkalemia Precipitated by Multiple Drug Interactions

Abstract: Voriconazole, a triazole antifungal agent used to treat serious fungal infections, has a pharmacokinetic characteristic of undergoing hepatic metabolism by the cytochrome P450 system. Few cases of hyperkalemia have been reported, which presented only when the serum voriconazole level was exceptionally elevated by drugdrug interactions. Additionally, azole antifungals may interfere with the biosynthesis of adrenal steroids and therefore can predispose patients to aldosterone deficiency. However, it is unclear w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In the treatment of CM, it is very important to reduce the incidence of adverse events. The reasons for the low incidence of hypokalemia in the AMB + 5-FC + VOR therapy may be as follows: (1) hypokalemia caused by AMB is dose-dependent [32,33], the total dosages of AMB in the AMB + 5-FC + VOR therapy were lower than that of the other two groups; (2) VOR is reported to cause hyperkalemia [34] and this may inadvertently counteract the potassium loss effect of AMB, thereby reducing the occurrence of hypokalemia. And the lower incidence of gastrointestinal discomfort in the AMB + 5-FC + VOR therapy might be associate with the shorter hospitalization time.…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment of CM, it is very important to reduce the incidence of adverse events. The reasons for the low incidence of hypokalemia in the AMB + 5-FC + VOR therapy may be as follows: (1) hypokalemia caused by AMB is dose-dependent [32,33], the total dosages of AMB in the AMB + 5-FC + VOR therapy were lower than that of the other two groups; (2) VOR is reported to cause hyperkalemia [34] and this may inadvertently counteract the potassium loss effect of AMB, thereby reducing the occurrence of hypokalemia. And the lower incidence of gastrointestinal discomfort in the AMB + 5-FC + VOR therapy might be associate with the shorter hospitalization time.…”
Section: Discussionmentioning
confidence: 99%
“…Voriconazole does not appear to induce the same pseudohyperaldosteronism as itraconazole,2 6 8 and should therefore be considered an alternative in patients experiencing this adverse effect to itraconazole. A recent report, however, has suggested that voriconazole under certain conditions and dosages may cause hypoaldosteronism and hyperkalaemia 9. Thus, serum potassium should also be monitored when treating with this drug.…”
Section: Discussionmentioning
confidence: 99%
“…Voriconazole has many well-described adverse effects such as visual disturbances, skin rashes, hallucinations, peripheral neuropathy, hepatotoxicity, nausea, vomiting and QT interval prolongation [6,7]. Electrolyte disturbances such as hyponatremia and hypokalemia are rarely reported [8,9]. By reviewing the literature, we found only three cases of voriconazole-associated hyperkalemia [5,10,11].…”
Section: Kidneymentioning
confidence: 99%
“…In our case, three hypotheses could explain the hyperkalemia: the atorvastatin-voriconazole interaction, the valsartan-voriconazole interaction or the own effect of voriconazole (probable elevated serum concentration mediated by significant inflammation of COVID-19). Atorvastatin is metabolized in the liver predominantly by the CYP3A4 isoenzyme and azole antifungals can increase serum statin concentrations by competing for catabolism [9]. High dose atorvastatin will induce rhabdomyolysis leading to onset of severe hyperkalemia due to renal failure [10,11].…”
Section: Figure 2 Blood Potassium Levels Before and After Oral Vorico...mentioning
confidence: 99%